2006
DOI: 10.1194/jlr.m500424-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate increases the formation of cytosolic lipid droplets and decreases the secretion of apoB-100 VLDL

Abstract: Epigallocatechin gallate (EGCG) increases the formation of cytosolic lipid droplets by a mechanism that is independent of the rate of triglyceride biosynthesis and involves an enhanced fusion between lipid droplets, a process that is crucial for their growth in size. EGCG treatment reduced the secretion of both triglycerides and apolipoprotein B-100 (apoB-100) VLDLs but not of transferrin, albumin, or total proteins, indicating that EGCG diverts triglycerides from VLDL assembly to storage in the cytosol. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…24 The relationship of hepatic TG accumulation and VLDL secretion is complex. 11,25 Overexpression of the nuclear forms of SREBP-1 represents an extreme situation leading to gross alterations of hepatic lipid metabolism not comparable to the present study, in which the observed effects on lipogenesis and SREBP-1c expression/maturation were relatively mild.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…24 The relationship of hepatic TG accumulation and VLDL secretion is complex. 11,25 Overexpression of the nuclear forms of SREBP-1 represents an extreme situation leading to gross alterations of hepatic lipid metabolism not comparable to the present study, in which the observed effects on lipogenesis and SREBP-1c expression/maturation were relatively mild.…”
Section: Discussionmentioning
confidence: 55%
“…24 The relationship of hepatic TG accumulation and VLDL secretion is complex. 11,25 Overexpression of the nuclear forms of SREBP-1 represents an extreme situation leading to gross alterations of hepatic lipid metabolism not comparable to the present study, in which the observed effects on lipogenesis and SREBP-1c expression/maturation were relatively mild.Insulin induces lipogenesis via phosphoinositide-3-kinase (PI-3-K) and Akt-dependent signaling cascades that upregulate SREBP-1c transcription. 26 -28 Moreover, insulin enhances the proteolytic activation of SREBP-1c and increases the half-life of nSREBP-1c.…”
mentioning
confidence: 55%
“…When they performed the first infection experiments with EGCG, a potent inhibition of HCV infection was noted, and the green tea molecule was identified as a novel HCV entry inhibitor (Ciesek et al, 2011). Calland and co-workers became interested in testing EGCG because it was reported to increase lipid droplet formation and to impair lipoprotein secretion in hepatocytes, two cellular functions known to play a role in the life cycle of HCV (Li et al, 2006). In these three studies it was clearly demonstrated that entry of cell culture-derived particles (HCVcc) as well as HCV pseudoparticles (HCVpp) are inhibited by EGCG independent of the HCV genotype (Ciesek et al, 2011;Calland et al, 2012;Chen et al, 2012).…”
mentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) inhibits growth of 3T3-L1 preadipocytes [21] or lipogenesis of 3T3-L1 adipocytes [22][23][24], whereas it increases the amount of cytosolic lipid droplets in NIH 3T3 and McA-RH7777 cells [25]. It has been reported that quercetin markedly inhibits lipogenesis in association with apoptosis in cancer cells [20], but it is uncertain whether quercetin affects the lipogenesis of adipocytes.…”
Section: Introductionmentioning
confidence: 98%